2019
DOI: 10.9744/jti.21.1.15-24
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Employee Performance in Hospitality Industry: The Role of Social Capital

Abstract: The hospitality industry is known for its labor-intensive and intense interpersonal relationships characteristic. The high rate of burnout in hospitality industry has been a crucial issue. The burnout could lead to employee performance decline. The previous studies suggested that the happy and cooperative employees tend to deliver a better performance. Since cooperative is a part of social capital, this study aims to analyse the role social capital in reducing burnout and improving employee performance.The dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…Among the demographic variables in this study, gender was significantly related to burnout, and women suffered more from burnout than men. This finding is consistent with most of the previous studies [ 19 , 29 , 30 , 31 ]. In this study, higher burnout in women may be influenced by a larger sample, but also because of the work pressures, work-family conflict situations that exposed working women to burnout-exacerbating factors, like severe psychological stress.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Among the demographic variables in this study, gender was significantly related to burnout, and women suffered more from burnout than men. This finding is consistent with most of the previous studies [ 19 , 29 , 30 , 31 ]. In this study, higher burnout in women may be influenced by a larger sample, but also because of the work pressures, work-family conflict situations that exposed working women to burnout-exacerbating factors, like severe psychological stress.…”
Section: Discussionsupporting
confidence: 94%
“…Among CTs, the relationship between social capital and burnout was further investigated in several studies, and the importance and preventive role of social capital had been emphasized [ 32 , 36 , 37 ]. The study results of Hador B 2016 and Harjanti D 2019 showed that social capital had a positive and significant effect on staff's task accomplishment, and increasing social capital would lead to increased task accomplishment [ 31 , 38 ]. Capital, in general, in all three types (social, cultural, and economic) played an essential role in preventing burnout.…”
Section: Discussionmentioning
confidence: 99%
“…After that, the data were analyzed through partial least squares with Smart PLS Software to know the validity and reliability of the model. , have a value of < 0.7 so that it must be removed in the model [24,25]. While the value of Composite Reliability, Variance Extracted (AVE), and Cronbach Alpha have been fulfilled so that it can proceed to the hypothesis testing stage [25].…”
Section: Methodsmentioning
confidence: 99%
“…Employees in the hospitality industry are frequently confronted with emotional demands from guests and may even be subjected to abusive behavior (Choo, 2017). In these troubled times, warm support from coworkers can help frontline employees to overcome their frustrations (Harjanti, 2019). Therefore, employees are more likely to recover from negative emotions and burnout, and engage in their work.…”
Section: Ijchm 3412mentioning
confidence: 99%